PERANCANGAN DESAIN INTERIOR POOL PERUSAHAAN OTOBUS PT. JAMBI PUTRA SEJAHTERA DI KOTA JAMBI - Drs. Suib Awrus, M.Pd., CACAH GUSTI HANDIKA, Ir. Drs. Heldi, M.Si. Ph.D., (Serupa The Journal of Art Education, 2017)
Interior design is akifitas art and spatial science, aims to create a functional space within the structure of the building. The purpose of design interior design pool company otobus PT. Jambi Putra Sejahtera in Jambi City is to build an effective spatial, and comfortable with aesthetic value that collaborated elements of decorative jambi area. Approach method in this design is the collection of verbal data, and visual, to the field with interviews, documentation, and literature study. After getting the necessary data, the author began to make preparations tobuild an interior design work in the form of a model with a scale of 1:30.The design result as the main idea is the design of the concept, design, lay out spatial, visible image, cut image, detail drawings, and spatial perspective, which completed the presentation model. The scientific contribution of this designcan be expected to build the attraction for the customer and build the image of PT. Jambi Putra Sejahtera in the city of Jambi.Keywords: design, interior, comfortable.